Disease-associated CAG·CTG triplet repeats expand rapidly in non-dividing mouse cells, but cell cycle arrest is insufficient to drive expansion - Gomes Prereira, Mario (2014)
Artículo científico -- Universidad de Costa Rica, Instituto de Investigaciones en Salud. 2014